2021
DOI: 10.3389/fsoc.2021.738024
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences and Lost Flexibility in Online Freelancing During the COVID-19 Pandemic

Abstract: We report findings from an ongoing panel study of 68 U.S.-based online freelancers, focusing here on their experiences both pre- and in-pandemic. We see online freelancing as providing a window into one future of work: collaborative knowledge work that is paid by the project and mediated by a digital labor platform. The study’s purposive sampling provides for both empirical and conceptual insights into the occupational differences and career plans of freelance workers. The timing of the 2020 data collection pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
(74 reference statements)
1
11
0
Order By: Relevance
“…In the interview, Chen said she had accepted the lockdown as a vacation, and meanwhile she prepared to get pregnant to 'accomplish the change of identity'. Discussions about (lost) work flexibility, uncertainty and gender during and post-Covid-19 are emerging worldwide (see Dunn et al, 2021), and the crossing-border reselling business model is one of many contextualised examples in the Chinese platform economy.…”
Section: Methodsmentioning
confidence: 99%
“…In the interview, Chen said she had accepted the lockdown as a vacation, and meanwhile she prepared to get pregnant to 'accomplish the change of identity'. Discussions about (lost) work flexibility, uncertainty and gender during and post-Covid-19 are emerging worldwide (see Dunn et al, 2021), and the crossing-border reselling business model is one of many contextualised examples in the Chinese platform economy.…”
Section: Methodsmentioning
confidence: 99%
“…The limited research has yielded mixed findings. Some studies found that because gig work offers higher flexibilities, gig workers could better schedule their work time; this was especially true for women who traditionally shoulder more domestic responsibilities (Altenried, 2020; Anderson & Bidwell, 2019; Churchill & Craig, 2019; Hall & Krueger, 2018) including during the COVID‐19 pandemic (Dunn et al, 2021). In addition, professionals may actively seek independent work to help maintain better work–family balance (McCallum et al, 2019).…”
Section: Themes and Issues In The Gig Work Literaturementioning
confidence: 99%
“…Some initial evidence points to gender differences in the gig work experience. Women may be more likely than men to choose gig work to fit their schedule (Churchill & Craig, 2019), and they were also more likely to reduce their gig hours during the COVID pandemic to take up more caregiving and other domestic responsibilities (Dunn et al, 2021). Gender may be associated with gig work income, as women are more likely to be sorted into low‐paying projects and less likely into high‐paying ones (Churchill & Craig, 2019; Fernandez‐Mateo & King, 2011).…”
Section: Moving Forward: Future Research Agendamentioning
confidence: 99%
See 1 more Smart Citation
“…The current evidence base is small, which is surprising given that there has been significant attention paid to the gendered nature of the pandemic in the traditional labour market. Dunn et al (2021) found significant gender differences in their small panel study of online freelancers, noting that women were more likely to report increased variability in earnings and decreased hours during the pandemic. Reynolds and Kincaid (2023) found that work-life-family conflict during the pandemic led to decreased work hours and pay but they do not unpack these findings by gender.…”
Section: Research Directions and Hypothesesmentioning
confidence: 99%